Role of Stock Market Development in Influencing the Performance of Non-financial Firms Listed on Pakistan Stock Exchange - Qasim, Saleem (Universiti Malaysia Sarawak (UNIMAS), 2019)
The emergence of the stock market development in Pakistan Stock Exchange leads to low business risk that affects the market value and performance decisions of the firms. It changes the market dynamics with a positive impact on the market conditions that makes it easy for the firms to make their performance’ decisions. This study aims to provide an extensive analysis of the role of the stock market development on different performance measures (Tobin Q, return on assets, return on equity and return on investment) of non-financial firms listed on Pakistan Stock Exchange from 2001 to 2017. This study used the two-step system Generalized Method of Moments (GMM) dynamic panel estimator for empirical testing of the hypothesis to investigate the performance of non-financial firms. Three different measures of the stock market development were used in this study, the first measure is stock market volatility (measured by two ways; standard deviation of the daily stock market index and GARCH of the daily stock market index), the second measure is the stock market capitalization (measured by total market capitalization as proportion of Gross Domestic Product (GDP) and the third measure is stock market liquidity (measured by total traded volume as a proportion of the GDP). This study used four measures of performance named as Tobin Q, return on assets, return on equity, and return on the investment of non-financial firms. The Stock market volatility significantly decreases the performance ratios along with the background theories like pecking order and trade-off theories. Firms with high stock market volatility bear the high cost of capital and choose low leverage to avoid financial distress cost. Besides, the stock market volatility shows a significant negative relationship with performance ratios. The results are based on robustness techniques of volatility and performance. The Stock market capitalization and stock market liquidity have positive significant relationship with firms performance. A well-developed stock market might decrease the information asymmetry in the market and firms to operate well in the market. It also increases the profits of the firms and they can retain their profits to meet their future investment needs. This study recommends policymakers and managers to devise a financial policy keeping in view of the stock market development for the better utilization of the funds in business. The findings also suggest a better policy to overcome the performance problems for non-financial firms facing the stock market developmental issues in Pakistan Stock Exchange. Keywords: Stock market, development, volatility, capitalization, liquidity, Pakistan Stock Exchange